Operatywna wykładnia prawa w warunkach multicentryzmu - Kotowski, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The paper analyses the notion of “polycentricism” of a legal system from the operational statutory interpretation perspective at two levels of discourse: the scientific one pertaining to the existing theories of statutory interpretation and the adaptive one pertaining to the statutory interpretation performed in the course of law application processes in the judicial domain. An argument is put forward that it is obvious that to a certain degree, statements formulated in particular circumstances within a framework of a theory of statutory interpretation are transferred to operational statutory interpretation practice. As a result, it is possible to analyse the degree of conformity between operational statutory interpretation and polycentric assumptions on two different planes, i. e. the degree to which the dominant contemporary theories of statutory interpretation take the assumptions of legal system’s “polycentricism” into account, and the degree to which if any these assumptions are subject to adaptation to influences from the statutory interpretation as performed in the course of law application processes in the judicial domain operativeness.
Keywords: teoria prawa; wykładnia prawa; multicentryzm